The Role of Google Classroom Application in Improving High School Student Achievement - Yusrianti, Susi; Guilin, Xie; Artanty, Ary; Jiao, Deng; Setyawan, Gogor Christmass (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Achievement is the highest achievement of a series of educational processes taken by students by relying on their intellectual and spiritual abilities. To improve student achievement, teachers can utilize existing technology, including the use of Google Classroom applications. The purpose of this study is to determine the role of the Google Classroom application in improving the achievement of high school students. The research method used is descriptive quantitative by conducting field research and data collection techniques by conducting in-depth interviews where researchers ask several questions to class teachers related to existing subjects, learning methods used, then the function of Google Classroom in the learning process, and things that can improve student achievement. The results of this case study explain that the use of Google Classroom applications can improve student achievement, this matter can be seen from the percentage count taken after conducting research. From the research conducted, it can be concluded that this application can be used as a medium for sending the results of assignments given by educators so that it can help improve student achievement. The limitation in this study is that researchers only know the role of Google Classroom applications in improving student achievement in only one school. Researchers hope that further research can conduct more in-depth research related to the role of Google Classroom applications in improving student achievement.